Progress in Location-Based Services - Krisp, Jukka M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The book consists of peer-reviewed papers from the 9th symposium on Location Based Services (LBS) which is targeted to researchers, industry/market operators and students of different backgrounds (scientific, engineering and humanistic). As the research field is developing and changing fast, this book follows up on current trends and gives suggestions and guidance to further research. This book offers a common ground bringing together various disciplines and practice, knowledge, experiences, plans and ideas on how LBS can and could be improved and on how it will influence both science and society. The book comprises front-end publications organized into sections on: spatial-temporal data acquisition, processing & analysis; positioning / indoor positioning; way-finding / navigation (indoor / outdoor) & smart mobile phone navigation; interactions, user studies and evaluations; innovative LBS systems & applications.
Extraction of location-based Emotions from Photo Platforms -- Combining Float Car Data and Multispectral Satellite Images to Extract Road Features and Networks for Navigation Applications -- Space-Time Mapping of Mass Event Data -- Analyzing Human Activities through Volunteered Geographic Information: Using Flickr to Analyze Spatial and Temporal Pattern of Tourist Accommodation -- A Platform for Location Based App Development for Citizen Science and Community Mapping -- A framwork for on-line detection of custom group movement patterns -- Mining Event Related Knowledge from OpenStreetMap -- Evaluation of Bluetooth properties for indoor localisation -- Pedestrian Indoor Localization Using Foot Mounted Inertial Sensors in Combination with a Magnetometer, a Barometer and RFID -- Quantitative and Spatial Evaluation of distance-based Localization Algorithms.
Keywords: Geography; Information systems; Geographical information systems; Geography; Geographical Information Systems/Cartography.; Information Systems and Communication Service